Histological analysis of tonsillectomies: relationship with surgical technique, post-operative pain and haemorrhage. Issue 12 (10th November 2016) - Magdalena, ML; Solé, A; Blanco, V; Rodrigo, JP
Abstract: Objectives: There is no consensus on the optimal technique to decrease post-tonsillectomy morbidity. Histopathological analysis can estimate collateral tissue damage. This study compared histological findings for tonsils removed by cold or electrocautery dissection and their relationship with post-operative complications. Methods: Two adult out-patient groups were included in the study: 37 who underwent cold dissection and 37 who underwent electrocautery dissection. Histological analysis was used to assess tissue damage. Results: Tissue damage was significantly higher in the electrocautery dissection group ( p = 0.002), as were the number of emergency department visits ( p = 0.01) and the need for supplemental analgesia ( p = 0.013). Patients in the cold dissection group experienced less pain ( p = 0.001) and fewer secondary haemorrhage episodes. Conclusion: Cold dissection produces less tissue damage, which is associated with lower incidence of complications. This study suggests that cold dissection is the technique of choice for tonsillectomy.